Clinical Outcomes Following Exercise Rehabilitation in People with Multimorbidity: A Systematic Review - Kathryn Barker; Anne E. Holland; Elizabeth H. Skinner; Annemarie L. Lee (Medical Journals Sweden, 2023)
Objective: To determine the effectiveness of exercise rehabilitation in people with multimorbidity. Exercise capacity was the primary outcome. Secondary outcomes were: health-related quality of life, activities of daily living, cardiometabolic outcomes, mental health outcomes, symptom scores, resource utilization, health behaviours, economic outcomes, and adverse events. Data sources: A search was conducted in MEDLINE, CINHAL, EMBASE, and Cochrane Central Register of Controlled Trials databases. Study selection and extraction: Randomized and non-randomized controlled trials and cohort studies of exercise rehabilitation vs any comparison in people with multimorbidity. Data synthesis: Forty-four reports (38 studies) were included. Rehabilitation ranged from 8 weeks to 4 years, with 1-7 sessions of rehabilitation weekly. Exercise included aerobic and resistance, limb training, aquatic exercises and tai chi. Compared with usual care, exercise rehabilitation improved 6-min walk distance (weighted mean difference (WMD) 64 m, 95% CI 45-82) and peak oxygen consumption (WMD 2.74 mL/kg/min, 95% CI -3.32 to 8.79). Effects on cardiometabolic outcomes and health-related quality of life also favoured rehabilitation; however; few data were available for other secondary outcomes. Conclusion: In people with multimorbidity, exercise rehabilitation improved exercise capacity, health-related quality of life, and cardiometabolic outcomes. LAY ABSTRACT Chronic disease is a common health problem worldwide. It is increasingly common for people to have more than 1 chronic disease, which is called multimorbidity, and the interaction of their multiple health problems may worsen their health outcomes. Exercise rehabilitation is an effective and established treatment to improve health for people with different chronic diseases, such as heart and lung disease; however, the benefit of structured rehabilitation in people with multimorbidity has not been systematically reviewed. A literature search was performed to investigate the clinical outcomes following exercise rehabilitation in people with multimorbidity. Compared with usual medical care, the results showed that exercise rehabilitation improved exercise capacity, measured by walking distance in a formal test, health-related quality of life and the body's ability to use oxygen, in people with multimorbidity. There were few data regarding the benefit of rehabilitation on other outcomes, and more well-designed robust trials are needed.